Genome-Wide Analyses of MADS-Box Genes Reveal Their Involvement in Seed Development and Oil Accumulation of Tea-Oil Tree (Camellia oleifera) - Xianzhi Zhang; Wenliang He; Xinyi Wang; Yongliang Duan; Yongjuan Li; Yi Wang; Qingbin Jiang; Boyong Liao; Sheng Zhou; Yongquan Li (International Journal of Genomics)
The seeds of Camellia oleifera produce high amount of oil, which can be broadly used in the fields of food, industry, and medicine. However, the molecular regulation mechanisms of seed development and oil accumulation in C. oleifera are unclear. In this study, evolutionary and expression analyses of the MADS-box gene family were performed across the C. oleifera genome for the first time. A total of 86 MADS-box genes (ColMADS) were identified, including 60 M-type and 26 MIKC members. More gene duplication events occurred in M-type subfamily (6) than that in MIKC subfamily (2), and SEP-like genes were lost from the MIKCC clade. Furthermore, 8, 15, and 17 differentially expressed ColMADS genes (DEGs) were detected between three developmental stages of seed (S1/S2, S2/S3, and S1/S3), respectively. Among these DEGs, the STK-like ColMADS12 and TT16-like ColMADS17 were highly expressed during the seed formation (S1 and S2), agreeing with their predicted functions to positively regulate the seed organogenesis and oil accumulation. While ColMADS57 and ColMADS07 showed increasing expression level with the seed maturation (S2 and S3), conforming to their potential roles in promoting the seed ripening. In all, these results revealed a critical role of MADS-box genes in the C. oleifera seed development and oil accumulation, which will contribute to the future molecular breeding of C. oleifera.